Reality and Negation - Kant's Principle of Anticipations of Perception An Investigation of its Impact on the Post-Kantian Debate - Giovanelli, Marco; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Kant, in the Critique of Pure Reason, only dedicates a few pages to the principle of Anticipations of Perception and only a few critical studies are outspokenly dedicated to this issue in recent critical literature. But if one considers the history of post-Kantian philosophy, one can immediately perceive the great importance of the new definition of the relationship between reality and negation, which Kant$1 (Bs principle proposes. Critical philosophy is here radically opposed to the pre-critical metaphysical tradition: "Reality" no longer appears as absolutely positive being, which excludes all negativity from itself, and "negation" is not reduced to being a simple removal, the mere absence of being. Instead, reality and negation behave as an equally positive something in respect to one another such that negation is itself a reality that is actively opposed to another reality. Such a definition of the relation between reality and negation became indispensible for post-Kantian Philosophy and represents a central aspect of Kantian-inspired philosophy in respect to Leibnizian metaphysics. The present work therefore departs from the hypothesis that the essential philosophical importance of the Anticipations of Perception can only be fully measured by exploring its impact in the Post-Kantian debate.s
1. From the Anticipationen der Wahrnehmung to the Dynamic Conception of Matter -- Anticipation as a priori Knowledge -- Perception and Sensation -- The Quantity of Quality: Degree or Intensive Magnitude -- The Two Formulations of the Principle -- The Category of Reality -- The Distinction between realitas phaenomenon and realitas noumenon -- The Critique of the Concept of Gradus Perfectionis -- From the Ontological Meaning to the Physical Meaning of the Concept of Degree -- Force and Sensation -- The Dynamic Conception of Matter 2. From Real Opposition to the Problem of Change -- Logical Opposition and Real Opposition -- Quantitative and Qualitative Opposition -- The Problem of Change -- Change and Real Opposition -- Change as Quantitative Variation -- Maimon$1 (Bs Theory of Differentials -- Change and Synthetic Unity. 3.The Anticipationen der Wahrnehmung in Post-Kantian Idealism -- Fichte and the opposition between the Self and the not-Self -- Schelling and the Philosophy of Nature -- The Problem of Quality and the Opposition between Positive and Negative -- Speculative Philosophy of Nature and Mathematical Philosophy of Nature -- The absolute as Quantitative Indifference -- Hegel and the "Mathematics of the Infinite" -- Being, Nothingness, and Becoming -- Herbart and Being as Pure Affirmation. 4. The Anticipationen der Wahrnehmung in Neo-Kantian Idealism.s
Keywords: Philosophy (General).; Philosophy, modern; Philosophy; History of Philosophy; Modern Philosophy